2001
DOI: 10.1111/j.1469-7793.2001.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Spark‐ and ember‐like elementary Ca2+ release events in skinned fibres of adult mammalian skeletal muscle

Abstract: Using laser scanning confocal microscopy, we show for the first time elementary Ca2+ release events (ECRE) from the sarcoplasmic reticulum in chemically and mechanically skinned fibres from adult mammalian muscle and compare them with ECRE from amphibian skinned fibres. Hundreds of spontaneously occurring events could be measured from individual single skinned mammalian fibres. In addition to spark‐like events, we found ember‐like events, i.e. long‐lasting events of steady amplitude. These two different fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
117
0
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(134 citation statements)
references
References 30 publications
13
117
0
4
Order By: Relevance
“…In resting skeletal fibers, inhibitory physical DHPR-RyR1 interactions prevent the development of spontaneous Ca 2ϩ sparks (46,47,59). Adult skeletal fibers show abundant sparks only after permeabilization, which collapses the membrane potential and weakens these physical DHPRRyR1 interactions (24,25,46,47,58,59). Supporting the functional evidence, electron microscopy (EM) studies (3,5,18,19,52) found a pattern of linkage between skeletal RyR channels (RyR1) at the terminal cisternae and DHPRs in T tubules of fast-twitch muscle.…”
mentioning
confidence: 51%
“…In resting skeletal fibers, inhibitory physical DHPR-RyR1 interactions prevent the development of spontaneous Ca 2ϩ sparks (46,47,59). Adult skeletal fibers show abundant sparks only after permeabilization, which collapses the membrane potential and weakens these physical DHPRRyR1 interactions (24,25,46,47,58,59). Supporting the functional evidence, electron microscopy (EM) studies (3,5,18,19,52) found a pattern of linkage between skeletal RyR channels (RyR1) at the terminal cisternae and DHPRs in T tubules of fast-twitch muscle.…”
mentioning
confidence: 51%
“…Such activity in these muscle preparations were attributed to the action of the type 3 RyR (Ward et al, 2000), an RyR isoform highly expressed in skeletal muscle during fetal development but only found in small quantities in adult muscle (Sutko et al, 1991). Until recently, significant numbers of Ca 2+ sparks were only observed in adult mammalian skeletal fibers following permeabilization of their sarcolemmal membrane with various physical or chemical methods (Kirsch et al, 2001;Zhou et al, 2003). Because of these intrinsic difficulties with monitoring CICR activity in intact mammalian skeletal muscle fibers, the cellular and molecular mechanisms underlying the regulation of CICR in skeletal muscle and the adaptive changes of CICR in muscle aging remain largely unknown.…”
Section: Differential Properties Of Ca 2+ Sparks In Cardiac and Skelementioning
confidence: 99%
“…5B). Some time courses displayed a repetitive firing pattern, whereas others showed a sustained fluorescence, reminiscent of long-duration Ca 2ϩ sparks seen previously (19,32), often preceded by a graded fluorescence increase and/or followed by a graded decrease in fluorescence.…”
Section: Ca 2ϩ Release Events In Line-scan Imagesmentioning
confidence: 99%